Challenges of Aircraft and Drone Spray Applications - Carvalho, Fernando K.; Chechetto, Rodolfo G.; Mota, Alisson A. B.; Antuniassi, Ulisses R. (Outlooks on pest management, 2020)
Crop protection on major crops is now required to follow the principles of integrated pest management so the timing and accuracy of any application of a pesticide or biopesticide has to be more precise to minimize adverse effects on non-target species. The development of UAVs (unmanned aerial vehicles) provides a means of providing a more targeted application of the correct dose, especially by using formulations that are more persistent, thus minimizing loss of spray in areas subject to rain. Avoiding use of too high a dosage allows greater survival of natural enemies and reduces the selection pressure for pests becoming resistant to specific modes of action. The downward flow of air from a UAV should also provide better distribution and impaction of droplets within a crop canopy, reduce soil impaction caused by taking heavy loads of spray applied with 200 l ha-1 of water, and allow treatments when fields are too wet to access with ground equipment. In Asia, many smallholder farmers are using a drone in preference to using a knapsack sprayer. According to Matthews, it has been shown that ULV spraying can be effective, but it needs a narrow droplet spectrum with the droplets remaining stable and not shrinking to become too small. Formulation research can reduce the volatility of the spray, hence the success of oil-based sprays. However, instead of petroleum-based oils, there is a chance to develop vegetable oil carriers with micro-sized particle suspensions to deliver low toxicity pesticides in droplets that can be deposited within the crop and not drift beyond the crop boundary. Oil deposits will be less prone to loss after rain so less should be lost in neighbouring ditches and water courses, especially as rainfall patterns are forecast to change. More studies are needed to evaluate the swath for deposition, buffer zones, formulation, nozzle selection, to guide future specific legislation for UAV applications.